A Study on the Dynamic Transmission Law of Spiral Drum Cutting Coal Rock Based on ANSYS/LS-DYNA Simulation. (3rd January 2019) - Zhao, Lijuan; Liu, Hongmei; Zhou, Wenchao
Abstract : The ANSYS/LS-DYNA software has been used in this paper to establish the coal rock coupling model. A dynamic simulation of the cutting process was used to analyze the variation of the load. Based on the dynamic analysis of the coal and rock that were cut by the spiral drum, the stress cloud diagram of the coupled model of the spiral drum and the coal and the plastic domain evolution law of the coal and the rock were obtained from the coal to the rock. The time history curves of the parameters, such as the stress and strain of the drum and the pick, were obtained, and the stress distribution of the spiral drum during the working process was ascertained. The results showed that when the spiral drum cuts the interface between the coal and the rock, the coal and the rock collapsed and the working load fluctuated. Changing the traction speed in order to change the rotational speed of the drum had a more obvious effect on the load and the stress on the drum. Through the use of simulation, the stress distribution cloud diagram of the drum was obtained. The study has shown that the stress on the end plate was significantly higher than that on the cutting blade. The maximum stress acting on the alloy head was 1209.26 MPa. This study has provided a basis for the design and optimization of the drum with regard to reliability.